2022
DOI: 10.3803/enm.2021.1282
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigens and Biomarkers in Type 1 Diabetes Mellitus Induced by Immune-Checkpoint Inhibitors

Abstract: Background: Type 1 diabetes mellitus induced by immune-checkpoint inhibitors (ICI-T1DM) is a rare critical entity. However, the etiology of ICI-T1DM remains unclear.Methods: In order to elucidate risk factors for ICI-T1DM, we evaluated the clinical course and immunological status of patients with ICI-T1DM who had been diagnosed during 2016 to 2021.Results: Seven of 871 (0.8%, six men and one woman) patients developed ICI-T1DM. We revealed that the allele frequencies of human leukocyte antigen (HLA)-DPA1*02:02 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
2
20
1
Order By: Relevance
“…However, other authors have also described an overrepresentation of T1DM protective haplotypes in patients with DM-ICIs (such as DR7, DR11 o DR15), which casts doubt on the real role of genetic predisposition in the pathogenesis of DM-ICIs [21]. This position is reinforced by the fact that DR9 (an HLA-II haplotype associated with Asian Fulminant Diabetes (AFD), which has a similar course to that of DM-ICIs) has not been found to be overrepresented [19,20,37]. Some authors have suggested the existence of different subtypes of DM-ICIs depending on the clinical and biochemical profile at the onset [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have also described an overrepresentation of T1DM protective haplotypes in patients with DM-ICIs (such as DR7, DR11 o DR15), which casts doubt on the real role of genetic predisposition in the pathogenesis of DM-ICIs [21]. This position is reinforced by the fact that DR9 (an HLA-II haplotype associated with Asian Fulminant Diabetes (AFD), which has a similar course to that of DM-ICIs) has not been found to be overrepresented [19,20,37]. Some authors have suggested the existence of different subtypes of DM-ICIs depending on the clinical and biochemical profile at the onset [25].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with our previous study (5), the current study was conducted on a larger scale with confirmation of HLA-DPB1*05:01 predominance in ICI-T1DM than those of general controls and ICIcontrols with the same ethnic background. Current study may also support other reports describing that HLA-DR4 alleles are increased in patients with ICI-T1DM in the United States (21,22), although these studies are not at the detailed allelic levels.…”
Section: Discussionmentioning
confidence: 79%
“…Immune-checkpoint inhibitors (ICIs) are effective agents in various cancers; however, immune-related adverse events (irAEs) often occur during treatment with ICIs (1)(2)(3)(4)(5). Major endocrine irAEs include pituitary irAE (3), thyroid irAE (4), and ICI-induced type 1 diabetes mellitus (ICI-T1DM).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations